In vitro antitrichomonal activity of Satureja khuzestanica and main essential oil components carvacrol, thymol, and eugenol - Karami, Faezeh; Dastan, Dara; Fallah, Mohammad; Matini, Mohammad (The Journal of Infection in Developing Countries, 2023)
Introduction: Human trichomoniasis is a widespread sexually transmitted disease and the concern of drug resistance in the parasite is growing. Hence, this study was performed to evaluate in vitro antitrichomonal activity of Satureja khuzestanica, carvacrol, thymol, eugenol, and phytochemical evaluation of the S. khuzestanica oil. Methodology: Extracts and essential oil of S. khuzestanica, and the components were prepared. Then, susceptibility testing was performed using the microtiter plate method and Trichomonas vaginalis isolates. The minimum lethal concentration (MLC) of the agents was determined in comparison with metronidazole. Also, the essential oil was investigated by gas chromatography-mass spectrometry and gas chromatography-flame ionization detector. Results: After 48 hours of incubation, carvacrol and thymol were the most effective antitrichomonal agents with MLC of 100 µg/mL, followed by the essential oil and hexanic extract (MLC = 200 µg/mL), then eugenol and methanolic extract (MLC = 400 µg/mL), in comparison with the metronidazole MLC of 6.8 µg/mL. Overall, 33 identified compounds accounted for 98.72% of the total essential oil composition with carvacrol, thymol, and p-cymene being the major constituents. Conclusions: The results suggested the potency of S. khuzestanica and its bioactive ingredients against T. vaginalis. Thus, further in vivo studies are required to evaluate the efficacies of the agents.